Umbilical Hernia In Adult: A Case Report - Yeppy Arief Nurzaman; Patrico Rillah Setiawan; Muhamad Rafdhi; Ririn Angelin Limbong; Fransiska Ayu Septiani Pratama Putri; Daniel Riskiandi (Rumah Sakit Unggul Karsa Medika, 2023)
Umbilical hernia is a disease process that still common in adults after inguinal hernia. An increased of intra-abdominal pressure causes hernia content to protrude through the weakness abdominal part. Umbilical hernia can be symptomatic and must be treated immediately to prevent complicati